Characteristics of the Antagonistic Fungus Nigrospora Oryzae Against the Fungus Fusarium as a Source of Biological Learning in Chili Plants - Yusuf, Moh. Ilham; Murtini, Iin (Jurnal Biologi Tropis, 2025)
One of the primary diseases that attack chilli plants (Capsicum annum) is Fusarium wilt, which is caused by the pathogenic fungi F. oxysporum and F. solani. This study aims to analyze the parasitism mechanism of the antagonistic fungus N. oryzae against the pathogen that causes Fusarium wilt in chilli. The method used was a dual culture technique antagonism power test with observations carried out every day from day 0 to day 5. The results of the study showed that the inhibition rate achieved was 33.3% against F. oxysporum and 18.18% against F. solani with the antagonism mechanism of N.oryzae, including 1) Mycoparasitism; 2) Degradation of pathogen cell wall;  3) competition for nutrients and space. The results showed that N. oryzae could inhibit the growth of F. solani and F. oxysporum. This proves that N. oryzae has the potential to be an effective antagonistic fungus in controlling both pathogens. The contribution of the results of the introduction of fungal antagonism is used as a learning resource to understand the concept of learning fungi through direct practical activities in the Laboratory.